Discharge on the day of surgery following unicompartmental knee arthroplasty within the United Kingdom NHS. (June 2017) - Bradley, B.; Middleton, S.; Davis, N.; Williams, M.; Stocker, M.; Hockings, M.; Isaac, D. L.
Abstract : Aims: Unicompartmental knee arthroplasty (UKA) has been successfully performed in the United States healthcare system on outpatients. Despite differences in healthcare structure and financial environment, we hypothesised that it would be feasible to replicate this success and perform UKA with safe day of surgery discharge within the NHS, in the United Kingdom. This has not been reported in any other United Kingdom centres. Patients and Methods: We report our experience of implementing a pathway to allow safe day of surgery discharge following UKA. Data were prospectively collected on 72 patients who underwent UKA as a day case between December 2011 and September 2015. Results: A total of 61 patients (85%) were discharged on the same day. The most common reason for failure was logistical; five patients had their operation too late in the day. Three patients failed to mobilise safely, two had inadequate control of pain and one had a leaking wound. The mean length of stay for those who were not discharged on the same day was 1.2 nights (1 to 3). During the same time, 58 patients underwent planned inpatient UKA, as they were deemed inappropriate for discharge on the day of surgery. However, three of these were safely discharged on the same day. Follow-up data, 24 hours post-operatively, were available for 70 patients; 51 (73%) reported no or mild pain, 14 (20%) had moderate pain and five (7%) had severe pain. There were no re-admissions. All patients had a high level of satisfaction. Conclusion: We found that patients can be safely and effectively discharged on the day of surgery after UKA, with high levels of satisfaction. This clearly offers improved management of resources and financial savings to healthcare trusts. Cite this article: Bone Joint J 2017;99-B:788–92.